Flumetralin and dimethyl piperidinium chloride alter light distribution in cotton canopies by optimizing the spatial configuration of leaves and bolls - Fu-bin LIANG; Cheng-xun YANG; Long-long SUI; Shou-zhen XU; He-sheng YAO; Wang-feng ZHANG (Journal of Integrative Agriculture, 2020)
Plant growth regulators (PGRs) are frequently used to adjust cotton growth and development. The objectives of this study were to determine how PGRs affect plant morphology, light distribution and the spatial distribution of leaves and bolls within the cotton canopy. The field experiments were carried out at Shihezi (Xinjiang Uyghur Autonomous Region, China) in 2014 and 2015. The experiment included two PGR treatments: (i) flumetralin (active ingredient (a.i.), N-N-ethyl-2,6-dinitro-4-aniline) and (ii) mepiquat chloride (a.i., 1-dimethyl-piperidiniuchloride) plus flumetralin. No PGR (manual topping) was applied in the control treatment. The chemically-topped plants were taller and had more main stem internodes than the manually-topped plants. Furthermore, the PGRs significantly reduced the length of fruiting branches in the upper canopy, resulting in a more compact canopy. The maximum leaf area index was significantly greater in the chemically-topped treatments than that in the control. In particular, the PGRs increased leaf area index by 25% in the upper canopy. The leaf area duration was also longer in the chemically-topped treatments than in the control. Compared with the control, the chemically-topped treatments increased canopy diffuse non-interceptance by 35.75% in the upper canopy layer, while reducing the fraction of intercepted photosynthetically active radiation by 14.45% in the upper canopy layer. Light transmittance in the upper and middle canopy layers was greater in the chemically-topped treatments than in the control, which increased boll numbers in both the upper canopy and the middle canopy. However, the chemically-topped treatments resulted in less light-leakage through the lower canopy layer during the late growth stages, which had a tendency to increase boll numbers in the whole canopy. In summary, the PGRs optimized canopy shape, light distribution and the spatial distribution of bolls and leaves.